An Antisense RNA-Mediated Transcriptional Attenuation Mechanism Functions in Escherichia coli - Brantl, Sabine (American Society for Microbiology, 2002)
Antisense RNA-mediated transcriptional attenuation is a regulatory mechanism operating in the replication control of two groups of plasmids in gram-positive bacteria, the pT181 group and the inc18 family, represented by pIP501. In contrast, this control mechanism has so far not been identified in gram-negative bacteria or their plasmids. In this work we asked whether such a mechanism can be supported by Escherichia coli. The core replication control regions of plasmids pT181 and pIP501 were transferred into this heterologous host. In vivo lacZ reporter gene assays showed that the antisense RNAs of these plasmids can inhibit lacZ expression and that most of this effect can be accounted for by reduced mRNA readthrough. Northern analyses confirmed that the ratio of attenuated to readthrough target RNA was increased in the presence of the cognate antisense RNA, as expected for this mechanism. Similarly, both antisense RNAs induced premature termination of their cognate target RNAs in an E. coli in vitro transcription system, whereas the noncognate antisense RNAs had no effect. Thus, this report shows that antisense RNA-mediated transcriptional attenuation is supported by at least one gram-negative host, although the data indicate that inhibitory efficiencies are lower than those for, e.g., Bacillus subtilis. Possible explanations for the apparent absence of this control mode in plasmids of gram-negative bacteria are discussed.